Unintentional Retinal Displacement in Eyes Treated for Rhegmatogenous Retinal Detachment Complicated by Proliferative Vitreoretinopathy with Pars Plana Vitrectomy and Silicone Oil - Mariaelena Filippelli; Pasquale Napolitano; Ciro Costagliola; Michele Rinaldi; Flavia Chiosi; Roberto dell’Omo (Journal of Ophthalmology)
Purpose. To examine the clinical characteristics, outcomes, and rate of unintentional displacement in eyes treated for rhegmatogenous retinal detachment (RRD) with pars plana vitrectomy (PPV) and silicone oil (SO). Methods. This retrospective observational study examined 50 eyes of 50 patients who underwent surgical repair for primary RRD complicated by proliferative vitreoretinopathy (PVR) by PPV and 1000-centistoke SO injection at a single institutional centre. The patients assumed a face-down posture immediately after surgery. Blue-fundus autofluorescence (B-FAF) pictures were obtained at 1 month after surgical procedures using a Spectralis HRA + OCT (Heidelberg Engineering, Heidelberg, Germany). Results. The primary success rate was obtained in 44 eyes (88%), on which the final analysis was conducted. Preoperative PVR was grade A in 7 eyes (15.9%), grade B in 28 eyes (63.6%), and grade C in 9 eyes (20.5%). The fovea was off and the detachment involved both the superior and inferior hemispheres of the retina in all cases. Breaks were located in the upper quadrants in 19 eyes (43.2%), in the lower quadrants in 12 eyes (27.3%), and in both upper and lower quadrants in 13 eyes (29.5%). The mean number of breaks was 3.4 ± 1.9. Intraoperative PFCL was used in 30 eyes (68.2%). Peeling of the epiretinal membrane/internal limiting membrane in the macula area was performed in 13 eyes (29.5%) during the first operation and carried out in all other eyes in occasion of SO removal. Preoperative BCVA was 2.1 ± 1.0 logMAR and improved to 0.8 ± 0.7 logMAR at the last follow-up (P<0.0001). An upward unintentional retinal displacement was observed in 2 cases (4.5%). Conclusion. PPV and SO tamponade for complicated RRD are associated with good anatomical and functional outcomes and a very low rate of unintentional retinal displacement. Of the factors potentially implicated in favouring displacement that were studied, none were found significant.